2017
DOI: 10.1186/s13046-017-0518-0
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA NKILA inhibits migration and invasion of non-small cell lung cancer via NF-κB/Snail pathway

Abstract: BackgroundNumerous studies have shown that long non-coding RNAs (lncRNAs) play key roles during multiple cancer processes, such as cell proliferation, apoptosis, migration and invasion. The previous studies found that NKILA interacted with and suppressed the nuclear translocation of NF-KappaB, which influenced metastasis and prognosis in breast cancer. However the clinical significance and biological role of NKILA in non-small cell lung cancer (NSCLC) remains unknown.MethodsWe examined expression levels of NKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 53 publications
2
113
0
Order By: Relevance
“…In nonsmall cell lung cancer, Lu et al 14 reported NKILA low-expression in cancer tissue samples was associated with lymph node metastasis and advanced TNM stage. In nonsmall cell lung cancer, Lu et al 14 reported NKILA low-expression in cancer tissue samples was associated with lymph node metastasis and advanced TNM stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nonsmall cell lung cancer, Lu et al 14 reported NKILA low-expression in cancer tissue samples was associated with lymph node metastasis and advanced TNM stage. In nonsmall cell lung cancer, Lu et al 14 reported NKILA low-expression in cancer tissue samples was associated with lymph node metastasis and advanced TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Moreover, Yang et al 18 demonstrated that knockdown of NKILA expression promoted cell viability and migration, and reversed cell apoptosis F I G U R E 4 The molecular mechanism of NKILA in rectal cancer cell. [14][15][16][17][18][19][20] In addition, NKILA was found to enhance the the anticancer effects of baicalein in hepatocellular carcinoma through modulating NF-κB signaling. B, NKILA overexpression inhibits p65 nuclear translocation and induces p65 cytoplasmic retention and the cytotoxicity of X-ray radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Since their discoveries, a large amount of lncRNA has been found being dysregulated in a range of cancers [5]. In addition, they are being identified and characterized for serial steps of cancer development, including tumor initiation, growth, and metastasis [6].…”
Section: Introductionmentioning
confidence: 99%
“…NF‐κB interacting LncRNA (NKILA), encoded by a gene at chromosome 20q13 just near by the prostate transmembrane protein androgen induced 1 (PMEPA1), was increased by NF‐κB in breast cancer . Recently, Lu et al discovered that NKILA expression was negatively associated with tumour metastasis in patients with NSCLC, and the expression of NKILA was regulated through classical TGF‐β signal pathway, which subsequently inhibited migration and invasion of NSCLC cells through interfering NF‐κB/Snail signal pathway in NSCLC cells …”
Section: Main Molecular Mechanism Of Lncrna To Regulate the Metastasimentioning
confidence: 99%